Antibacterial, Antifungal and Cytotoxic Properties as well as Molecular Docking Evaluation of Green Synthesized Silver Nanoparticles - Mojgan Taebi; Mahnaz Amiri; Niloofar Rashidi; Mahsa Sistani; Sanaz Hadizadeh; Razieh Razavi; Ali Reza Farzinnejad; Meysam Ahmadi Zeidabadi; Somayeh Karami Mohajeri (Nanochemistry Research)
The utilization of silver nanoparticles (AgNPs) in diverse fields, including medicine, is on the rise, leading to the development of a non-toxic and environmentally friendly synthesis method. This study presents a straightforward and stable one-step synthesis of AgNPs using an aqueous extract of Amygdalus lycioides as both a reducing and stabilizing agent. The experimental findings demonstrated that the presence of Amygdalus lycioides extract results in the formation of AgNPs with smaller size, uniformity, and well-dispersed nanostructures. The synthesis process is significantly influenced by certain reaction parameters such as the molar ratio of AgNO3, temperature, and extract volume. Characterization of the nanostructures was performed using XRD, UV-Vis, FT-IR, DLS, and SEM measurements. Furthermore, the AgNPs exhibited potent antibacterial effects, leading to cell death through increasing the membrane permeability and disrupting bacterial wall integrity. Additionally, this research explores the fungicidal characteristics of the colloidal solution of nanosized silver as a potential antifungal treatment against various plant pathogens. Based on the obtained results, AgNPs exhibit varying levels of antifungal activity against these plant pathogens. Molecular docking calculations revealed the binding energy between Ag metal and bacteria. These findings pave the way for effective and novel antimicrobial therapies as alternatives to traditional antifungal and antibacterial drugs, thereby addressing the challenges of microbial resistance and the difficulty of eradicating infections in the near future.